Dilemmas of Classifying Difference: the Promises and Disruptions of Inclusive Education Across Cultural Contexts - Marta Z. CABALLEROS; Alfredo J. ARTILES; Daniela GAMBOA-ZAPATEL (Revista Brasileira de Educação Especial, 2024)
ABSTRACT The call for expanding educational opportunities for all (including the most vulnerable groups) has been both promising and disruptive, particularly as inclusive education policies spread across the globe. Notably, inclusive education embodies a transformative promise for contexts where inequality is ubiquitous. However, different perspectives on the categorization of vulnerable groups are emerging around the globe, which influences the way Inclusive Education is designed and implemented. Thus, in this paper, we reflect on the differences among countries in their approach to implementing Inclusive Education, we discuss the hierarchies of difference that are created, and we set an initial discussion to foster the analysis of categories of difference and their implications for Inclusive Education in future research.